The effect of occlusal balance and prosthesis on occlusal function of patients after dental implant restoration - Yanli Zhang; Baorong Zhang (Heliyon)
Objective: This observational study investigated the relationship between occlusal balance and the tightness of restorative-contralateral occlusal contact in patients undergoing dental implant restorations. Methods: A total of 100 patients who received dental implant restorations at our hospital between July 2022 and July 2023 were included. Patients were divided into two groups based on occlusal closeness: an observation group (using 12 μm occlusal paper for occlusion) and a control group (using 20 μm occlusal paper for occlusion). Various indexes including peri-implant bone resorption, periodontal pocket depth, gingival index, and tooth looseness were compared between the groups. Absolute values of occlusal balance indexes were compared before restoration, on the day of restoration, and 3 months after restoration. Correlation analysis was conducted to examine the relationship between occlusal balance, occlusal closeness, and restoration time. Results: Results showed no significant differences in peri-implant bone resorption, periodontal pocket depth, gingival index, or tooth looseness between the groups. The absolute value of the occlusal balance index in the observation group was remarkably lower than that in the control group 3 months after repair. After correlation analysis, there was no apparent correlation between the absolute value of the occlusal balance index and the degree of occlusal tightness of the patients. However, there was a clear negative correlation between the absolute value of the occlusal balance index and the repair time. Conclusion: In conclusion, using 12 μm occlusal paper for mandibular teeth appears to facilitate restoration of occlusal balance after dental implant restoration.